ADV-Based Investigation on Bed Level Changes Over a Meso-Macro Tidal Beach - Pang, Wenhong; Zhou, Xiaoyan; Dai, Zhijun; Li, Shushi; Huang, Hu; Lei, Yaping (Frontiers in Marine Science, 2021)
Beach intra-tidal bed level changes were of significance to coastal protection behind global climate changes. However, due to the limitation of instruments and the disturbance induced by wave motions superimposed on water level, it was difficult to detect the high-frequency oscillation of submerged beach bed level. In this study, an observation, lasting for 12 days and covering middle tide to the following spring tide, was conducted over a meso-macro tidal beach, Yintan Beach, to simultaneously detect the characteristics and influence mechanism of bed level changes at intra-tidal and tidal cycle scales. The collected data included water depth, suspended sediment concentration (SSC), waves, high-frequency 3-D velocity and distance of seabed to ADV probe, which were measured by an Optical backscatter sensor, two Tide & Wave Recorder-2050s and an acoustic Doppler velocimeter (ADV), respectively. The results showed that tidal cycle-averaged bed level decreased by 58.8 mm, increased by 12.6 mm and increased by 28.9 mm at neap, middle and spring tides in succession, respectively, compared with preceding tidal regimes. The net erosion mainly resulted from large incident wave height and the consequent strong offshore-directed sediment transport induced by undertow. Moreover, the variations of bed level were more prominent during neap to middle tides than during middle to spring tides, which was jointly caused by wave breaking probability regulated by water depth and relative residence times of shoaling wave, breaker and surf zones that were determined by relative tidal range. In terms of intra-tidal bed level, it displayed an intra-tidal tendency of increase during flood and decrease during ebb tides, i.e., the intra-tidal bed level changes were controlled by water depth, which modulated the effects of waves on sediment resuspension and vertical sediment exchange. In specific, waves and SSC were responsible for the intra-tidal bed level changes under low energy wave condition, while mean current and bedform exerted important influences on the variations of intra-tidal bed level under moderate wave condition, which broke the foregoing interrelation between bed level, waves and SSC. The study therefore emphasizes the usage of ADV measurement to investigate bed level changes in sandy coasts.